PENERAPAN MODEL PEMBELAJARAN INQUIRY TRAINING BERBANTU VEE DIAGRAM TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA KELAS X PADA KONSEP EKOSISTEM - Inati, Hertika Dhea; Abidin, Zaenal; Junaedi, Edi (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2016)
The background of this research is about learning process that refers to teacher centered. It makes students become passive in the classroom, so they are lazy to think creatively even to ask something they don’t understand to the teacher. The aim of this research is to know the influence of applying inquiry training learning model assisting vee diagram toward students’ creative thinking. In this research, the population is all of tenth grade students at SMA Negeri 1 Kuningan in academic year 2015/2016 that consists of five classes with 192 students. Technique of selecting sample used in this research is cluster random sampling. The sample consists of one experimental class and one another is control class. The researcher uses quasi experimental method, namely posttest-only control design. Instrument that is used in this research is essay test to know students’ creative thinking skill, questionnaire that is used to know students’ responses toward inquiry training learning model, and observation field that is aimed to know the applying of inquiry training learning model on each syntax. The data then analyzed by using t-test since the two variances are homogeny. From posttest cultivation through t-test in 99% of credibility level, it is gained tcount 2,72 and ttable 2,65, so tcount ttable. So, H1 is accepted that means there is a significant influence from applying inquiry training learning model assisting vee diagram toward students’ creative thinking skill in ecosystem concept. It is because vee diagram can help students in increasing their knowledge, analyzing information, stimulating students’ awareness, creating a detail work plan, creating inquiry plot becomes more directed, and helping inquiry training learning process becomes more powerful so that it can encourage students to think creatively.Keywords: Inquiry Training, Vee Diagram, Students’ creative thinking skill, Ecosystem